VASCULAR VARIATIONS IN THE CALOT’S TRIANGLE SEEN ON LAPAROSCOPIC CHOLECYSTECTOMY - Hasan, Azmat; Taimur, M.; Ullah, Sami; Masood, Rehan; Imran, M. (Pakistan Armed Forces Medical Journal, 2011)
Objectives: To describe the frequency and pattern of vascular variations seen in the Calot’s triangle on laparoscopic cholecystectomy. Study Design: Descriptive study. Place and Duration: From December, 2008 to February, 2011. Surgical Unit 1, Fauji Foundation Hospital, Rawalpindi. Patients and Methods: Two hundred patients with a diagnosis of biliary colic, cholelithiasis, acute cholecystitis, empyema gall bladder and mucocele gall bladder were included. Patients with age less than 15 years were excluded. Careful dissection of the Calot’s triangle was carried out. The anatomical variations of the cystic artery and other anomalous variations in the region were noted and data analyzed on SPSS 10. Results: The age range was 19 to 88 years with a mean of 48 years. The majority (88%) of the patients presented with a clinical diagnosis of biliary colic. The cystic artery was single in 91%, branched in 6% and absent in 3% cases. The cystic artery was supero-medial to the cystic duct in 88%, anterior in 6%, and posterior in 3% of the cases. Other arterial variations included Calot’s arteries (2%), Moynihan’s Hump (3%) and gall bladder arterial supply from liver bed (3%). Conclusions: Each Calot’s triangle differs from the other. Vascular variations are the hallmark of this region and their knowledge is mandatory for a safe laparoscopic cholecystectomy.